Carrying offspring: An unknown behavior of armadillos - Soibelzon, Esteban (Therya Notes, 2020)
Armadillos are the only extant mammals characterized by bony shielded regions that protect their head, body, and tail. They have been found exclusively in the Americas. Reproduction is seasonal (from late winter and throughout the entire austral spring and summer, i.e., September to March). During mating season two to four males attempt to mate with a single female, after mating the female raises the offspring alone. Parental care are practically unknown among armadillos. This contribution describes and document for the first time (both by photos and video) the carrying of young offspring by Chaetophractus villosus and Zaedyus pichiy at different locations of Argentina and Chile, most of them were obtained by citizen science. In all cases the adult catch their pup with its mouth, from its right or left forelimb (one case from the border of the pup scapular shield). Due to all cases are temporally and geographically disconnected, and was observed in different species, this behavior could be part of the usual parental care of armadillos. This results shows the importance of the citizen science for data collection, especially to gain new information about criptic species or uncommon behavior.